2009
DOI: 10.4197/islec.22-1.1
|View full text |Cite
|
Sign up to set email alerts
|

Home Financing through the Musharakah Mutanaqisah Contracts: Some Practical Issues

Abstract: Abstract. The authors compare the al-Bay' Bithaman Ajil (BBA) and the Musharakah Mutanaqisah Partnership (MMP) contracts. The BBA, a murabahah contract, was argued to be problematic and even unIslamic for long-duration contracts. The MMP contract which is a combination of musharakah (partnership) and ijarah (rental) contracts was argued to be a more appealing alternative. In the MMP, the equity of the financier diminishes progressively while, in accordance, the equity of the customer grows. Unlike for the BBA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(107 citation statements)
references
References 1 publication
4
102
0
1
Order By: Relevance
“…In the study done by Meera and Razak (2005), they compared the home financing package between BBA and MMP and they concluded that MMP home financing is a better alternative compare to BBA home financing. They argued that the profit rate of BBA is fixed and it also follows the similar computation in the interest based system.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In the study done by Meera and Razak (2005), they compared the home financing package between BBA and MMP and they concluded that MMP home financing is a better alternative compare to BBA home financing. They argued that the profit rate of BBA is fixed and it also follows the similar computation in the interest based system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…She also compares the structures of BBA and MMP, the problems and risks faced in practicing the contracts and also their acceptance in the Shariah. Meera and Razak (2009) further explained the issues encountered in practising MMP contract. They found out that the banks are replacing the rental rate with market interest rate of which interest should be avoided in real Islamic banking and the rental rate supposed to be determined by the market rental of the property divided by the value of property.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations